Effect of Direct Viral–Bacterial Interactions on the Removal of Norovirus From Lettuce - Xu, Zhangkai; Liu, Zishu; Chen, Jiang; Zou, Songyan; Jin, Yan; Zhang, Ronghua; Sheng, Yaqi; Liao, Ningbo; Hu, Baolan; Cheng, Dongqing (Frontiers in Microbiology, 2021)
Norovirus is the main non-bacterial pathogen causing outbreaks of gastroenteritis and is considered to be the leading cause of foodborne illness. To determine whether lettuce-encapsulated bacteria can express HBGA-like substances to bind to norovirus and if so, to explore its role in protecting norovirus from disinfection practices.15 bacterial strains (HBGA-SEBs) were isolated from the lettuce microbiome and studied as they were proved to have the ability to express HBGA-like substances through indirect ELISA detection. By using attachment assay, HBGA-SEBs showed great abilities in carrying NoVs with regarding the evaluation of binding capacity, especially for the top four strains from genera Wautersiella, Sphingobacterium, Brachybacterium, which could absorb more than 60% of free-flowing NoVs. Meanwhile, the directly viral-bacterial binding between HBGA-SEB and NoVs was observed by the TEM. Subsequently, results of simulated environmental experiments showed that the binding of NoVs with HBGA-SEBs did have detrimental effects on NoVs reduction which were evident in short-time high-temperature treatment (90℃) and UV exposure. Finally, by considering the relative abundance of homologous microorganisms of HBGA-SEBs in the lettuce microbiome (c.a. 36.49%) and the reduction of NoVs in the simulated environments, we suggested putting extra attention on the daily disinfection of foodborne-pathogen carriers to overcome the detrimental effects of direct viral-bacterial interactions on the reduction of NoVs.